Pregnancy and delivery outcomes from patients with repaired anomalous origin of the left coronary artery from the pulmonary artery. Issue 5 (5th February 2018) - Kanoh, Miki; Inai, Kei; Shinohara, Tokuko; Shimada, Eriko; Shimizu, Mikiko; Tomimatsu, Hirofumi; Ogawa, Masaki; Nakanishi, Toshio
Abstract: Aim: We investigated the clinical courses before and during pregnancy and after delivery in patients with repaired anomalous origin of the left coronary artery from the pulmonary artery to determine the impact of the hemodynamic changes and cardiac function on the selection of the appropriate mode of delivery. Methods: Six patients who underwent coronary artery reimplantation delivered 10 infants. We scrutinized the patients' hemodynamic changes on echocardiographs and the plasma brain natriuretic peptide levels before and during pregnancy and after delivery, the perinatal outcomes and maternal and fetal events. Results: All patients were asymptomatic and categorized as having New York Heart Association functional class I before pregnancy. In 8 of 10 pregnancies, vaginal deliveries were performed; two elective cesarean sections were performed because of symptomatic heart failure. The hemodynamic parameters were stable throughout pregnancy and postdelivery, and no maternal or fetal events occurred in the patients who underwent vaginal deliveries. One cesarean section patient developed significant heart failure during the late second and third trimesters, which was accompanied by hemodynamic changes, including increased brain natriuretic peptide levels, left ventricular diastolic dysfunction and worsening arrhythmias, and thrombosis and post‐partum hemorrhage occurred postdelivery. The baby had intrauterine growth retardation and small for gestational age. None of the babies had congenital anomalies. Conclusion: Pregnancy was safe in most of the asymptomatic patients long after anomalous origin of the left coronary artery from the pulmonary artery was repaired. Symptomatic heart failure might occur during pregnancy in patients with persisting myocardial damage. Pregnancy and delivery should be carefully managed.